Building a measure of competitive driving behavior of handball coaches from the point of view of players of first-class clubs in Iraq - Khudhair, Ahmed; Hussain, Fouad (Journal of Physical Education, 2023)
The current research aims to build a measure of competitive driving behavior of a handball coach from the point of view of the players of first-class clubs in Iraq to be able to know the behavior of each coach during the events of the matches and to know the strengths and weaknesses of that behavior, After the two researchers reviewed the metrics and literature in the subject of sports management and organization, which presented the topic of leadership behavior, it was noticed that there is an urgent need to study this behavior during sports competition, and everything related to the events of the match and more accurately, away from variables outside the sports competition because of its significant immediate impact on the performance and results of the team, And here the problem of research lies in knowing the behavior that coaches follow with the players during the competition in order to reach the goals, and the purposes that he seeks to succeed, and the descriptive approach was used in a survey way to suit the nature of the problem, as the research sample consisted of players of first-class clubs for a period from 1-1-2023 until 1-4-2023. The researchers concluded that handball coaches in the first division possess a good level of leadership during sports competition due to the accumulated experience, as the researchers recommended conducting a similar study of the subject with different samples.